HOW TO BEGIN? - Navndrup Black, Laura (Peripeti, 2024)
Through a practice-near unfolding of the research project Imagining (the Imagination of) the Other, I advocate for renewed approaches when it comes to inviting people who are not (yet) professional dancers into choreographic processes; rather than adapting or simplifying the work for all to join, I suggest delving into the complexity of the artistic proposal, allowing unforeseen logics to surface.